The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/insects10050143
|View full text |Cite
|
Sign up to set email alerts
|

Fine Morphology of the Mouthparts in Cheilocapsus nigrescens (Hemiptera: Heteroptera: Miridae) Reflects Adaptation for Phytophagous Habits

Abstract: To obtain a better understanding of feeding adaptations, the fine structure of the mouthparts in adults of Cheilocapsus nigrescens Liu and Wang, including the sculpture and interlocking mechanisms of the stylets and distribution and abundance of sensilla located on the labium, were studied using scanning electron microscopy. The mouthparts are similar to those of previously studied mirid species in most aspects and composed of a cone-shaped labrum, a tube-like, four-segmented labium with a deep groove on the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 39 publications
5
19
0
Order By: Relevance
“…The labrum of E. fullo corresponds to the second group. This is similar to other true bugs, e.g., Pyrrhocoris sibiricus [52], Cheilocapsus nigrescens [53], and four species of Largidae (Physopelta quadriguttata, Ph. gutta, Ph.…”
Section: Mouthpart Morphology and Their Adaptability To Feedingsupporting
confidence: 79%
See 4 more Smart Citations
“…The labrum of E. fullo corresponds to the second group. This is similar to other true bugs, e.g., Pyrrhocoris sibiricus [52], Cheilocapsus nigrescens [53], and four species of Largidae (Physopelta quadriguttata, Ph. gutta, Ph.…”
Section: Mouthpart Morphology and Their Adaptability To Feedingsupporting
confidence: 79%
“…To our knowledge, this is the first time that the detailed mouthpart morphology and feeding performance in a member of Pentatomidae have been reported together. The modified mouthparts of E. fullo have a number of morphological similarities to those heteropteran species described previously [17,19,22,37,44,[48][49][50][51][52][53][54][55], but our study revealed some new and interesting features that differ from those of other true bugs, and provide a better understanding of the feeding strategies and the sensory systems of E. fullo.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations